2020
DOI: 10.4094/chnr.2020.26.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Breastfeeding Support Program on the Prevalence of Exclusive Breastfeeding and Growth in Late Preterm Infants

Abstract: Purpose: The purpose of this study was to investigate the effects of a breastfeeding support program (BSP) on the prevalence of exclusive breastfeeding and growth in late-preterm infants.Methods: A quasi-experimental study was conducted. The participants were 40 late preterm infants (LPIs), of whom 20 were assigned to the experimental group and 20 to the control group. For the mothers in the experimental group, a BSP was provided prior to the LPIs’ discharge and reinforced once a week for 4 weeks. Information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 22 publications
4
8
0
Order By: Relevance
“…This discrepancy indicates that Korean LPIs are less likely to be continued to be breastfed than LPIs in other nations. This result is consistent with a study on a breastfeeding support program provided for LPIs, which showed that the exclusive breastfeeding rate in the experimental group (55%; n=20) was higher than that in the control group (25%; n=20) at the fourth week [17]. In the study by Jang and Hong [17], the higher exclusive breastfeeding rate than was observed in this study reflected the conditions of the LPIs.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This discrepancy indicates that Korean LPIs are less likely to be continued to be breastfed than LPIs in other nations. This result is consistent with a study on a breastfeeding support program provided for LPIs, which showed that the exclusive breastfeeding rate in the experimental group (55%; n=20) was higher than that in the control group (25%; n=20) at the fourth week [17]. In the study by Jang and Hong [17], the higher exclusive breastfeeding rate than was observed in this study reflected the conditions of the LPIs.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with a study on a breastfeeding support program provided for LPIs, which showed that the exclusive breastfeeding rate in the experimental group (55%; n=20) was higher than that in the control group (25%; n=20) at the fourth week [17]. In the study by Jang and Hong [17], the higher exclusive breastfeeding rate than was observed in this study reflected the conditions of the LPIs. Specifically, 50% of the LPIs in both groups in the study by Jang and Hong [17] were recruited from a nursery and had relatively fewer health issues, whereas the LPIs in this study were recruited from the NICU alone.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations